2020
DOI: 10.1177/1120672120901701
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms and associated factors in an urban, ophthalmic population

Abstract: Objective: To determine the prevalence of depressive symptoms in an adult ophthalmic patient population and to delineate correlates. Design: Cross-sectional study. Participants: Adult patients (⩾18 years) were approached in general and sub-specialty cornea, retina, and glaucoma ophthalmic clinics. A total of 367 patients from the four clinics were enrolled. Methods: Depressive symptoms were assessed using the Patient Health Questionnaire-9. A cut-off score of ⩾10 was used to indicate clinically significant dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…4,5,31 Besides high rates of physical comorbidity, people with visual impairments are at risk for poor mental health outcomes. [9][10][11] Importantly, approximately 68% of vision impairment is avoidable. 167 While blindness as a result of age-related disease (eg, AMD, diabetic retinopathy, glaucoma) is not reversible at this point, many impairments can be corrected or altogether avoided 131 with better attention to eye health, and doing so should prevent development of some mental health problems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,5,31 Besides high rates of physical comorbidity, people with visual impairments are at risk for poor mental health outcomes. [9][10][11] Importantly, approximately 68% of vision impairment is avoidable. 167 While blindness as a result of age-related disease (eg, AMD, diabetic retinopathy, glaucoma) is not reversible at this point, many impairments can be corrected or altogether avoided 131 with better attention to eye health, and doing so should prevent development of some mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…A sizable body of literature suggests that people with vision impairment are at increased risk for specific mental health problems. In particular, a number of studies have demonstrated a link between vision impairment and depression (eg, [9][10][11] ). Nearly one third of individuals with visual impairments and disabling eye diseases experience mild depressive symptoms, 12 while 10.7-45.2% of study samples report clinically significant (ie, moderate-to-severe) depressive symptoms.…”
Section: Part I: Vision Loss and Mental Health Depression In Visuallymentioning
confidence: 99%
See 3 more Smart Citations